The central executive system of working memory and primary memory deficits in patients with probable Alzheimer's disease. - Curwin, Robbie D. (University of Ottawa (Canada), 2000)
Alzheimer's disease is an insidious neurodegenerative disorder characterized by gradual and progressive deterioration in intellect, cognitive skills, personality, and functional independence. There is significant heterogeneity of symptom presentation in the early stages of Alzheimer's disease, however, memory impairment is universal. Both secondary and primary memory systems are consistently reported in the literature to be affected by the disease. Primary memory is considered a limited capacity system characterized by a rapid rate of forgetting. Historically, primary memory was thought to be a unitary system necessary for the transfer of information into secondary memory and underlying a range of cognitive functions such as reasoning and language comprehension. However, research over the past decade has suggested an important role of a deficient putative central executive system in working memory as fundamental to the deficits in primary memory demonstrated by patients diagnosed with Alzheimer's disease. Working memory is defined by two primary memory storage systems, the phonological loop, and the visuospatial sketchpad, controlled and organized by a central executive system. Research with respect to working memory in patients diagnosed with Alzheimer's disease has shown the phonological loop and visuospatial sketchpad to remain unaffected by the disease process during the mild stages of the disorder. Thus, deficits in primary memory were ascribed to a faulty central executive system. However, few, if any, empirical studies directly relating deficient primary memory with executive system dysfunction are available. The goal of this dissertation is aimed at providing empirical validation that executive system dysfunction underlies the primary memory disturbance in a sample of patients diagnosed with probable Alzheimer's disease within the mild stages of dementia. Performance on measures of primary such as Digit Span and the Consonant Trigrams Test were compared amongst patients identified with a possible executive system disturbance, patients assumed to have executive functions relatively intact, and normal controls. Furthermore, Alzheimer's disease patients and normal controls were compared on the Random Generation Task, assumed to be the prototypical measure of central executive functioning in working memory. The data supports the hypothesis that executive system disturbance may explain the difficulties that Alzheimer's patients have on measures of primary memory. Those patients identified with a putative executive system disturbance performed significantly worse on all measures of primary memory compared to those Alzheimer's patients assumed to have a relatively intact executive system. Furthermore, those Alzheimer's patients identified as having no executive dysfunction performed similarly to normal controls on measures of primary memory, thus further supporting the role of executive system disturbance in deficient primary memory functioning. Performance on the Random Generation Task also followed a similar pattern in that those patients with an assumed executive system disturbance performed significantly worse than those patients with a relatively intact executive system and normal controls. The current findings are discussed in the context of the working memory model proposed by Baddeley and Hitch in 1974.
Keywords: Psychology, Clinical.